Question and Answers Forum

All Questions      Topic List

Geometry Questions

Previous in All Question      Next in All Question      

Previous in Geometry      Next in Geometry      

Question Number 53252 by ajfour last updated on 19/Jan/19

Commented by ajfour last updated on 19/Jan/19

Find a and r in terms of b.

Findaandrintermsofb.

Answered by tanmay.chaudhury50@gmail.com last updated on 19/Jan/19

  centreA is (x−0)^2 +(y−b)^2 =a^2   centre B is (x−a−b)^2 +(y−b)^2 =b^2   AC=(√((r−0)^2 +(r−b)^2 )) =r+a  r^2 +r^2 −2rb+b^2 =r^2 +2ra+a^2   r^2 −2rb+b^2 −2ra−a^2 =0....eqn 1  BC  (a+b−r)^2 +(b−r)^2 =(r+b)^2   a^2 +b^2 +r^2 +2ab−2ar−2br+b^2 −2br+r^2 =r^2 +2br+b^2   a^2 +2b^2 +2r^2 +2ab−2ar−4br−r^2 −2br−b^2 =0  a^2 +b^2 +r^2 +2ab−2ar−6br=0....eqn 2  r^2 −2ra−a^2 =2rb−b^2  frlm 1  r^2 −2ar+a^2 =6br−2ab−b^2   from 2  r^2 −2ra+b^2 =a^2 +2rb  r^2 −2ra+b^2 =6br−2ab−a^2   so  a^2 +2rb=6br−2ab−a^2   2a^2 −4br+2ab=0  r=((2a^2 +2ab)/(4b))=((a(a+b))/(2b)) ←  r^2 −2ar−a^2 =2rb−b^2   (((a^2 +ab)/(2b)))^2 −2(a+b)(((a^2 +ab)/(2b)))=a^2 −b^2   ((a^2 (a+b)^2 )/(4b^2 ))−(((a+b)(a+b)a)/b)=(a+b)(a−b)  deviding by a+b both side  ((a^2 (a+b))/(4b^2 ))−((a(a+b))/b)=a−b  (a+b)((a^2 /(4b^2 ))−(a/b))=a−b  (a^2 /(4b^2 ))−(a/b)=((a−b)/(a+b))   let (a/b)=k  (k^2 /4)−k=((k−1)/(k+1))  ((k^2 −4k)/4)=((k−1)/(k+1))  k^3 −4k^2 +k^2 −4k=4k−4  k^3 −3k^2 −8k+4=0

centreAis(x0)2+(yb)2=a2centreBis(xab)2+(yb)2=b2AC=(r0)2+(rb)2=r+ar2+r22rb+b2=r2+2ra+a2r22rb+b22raa2=0....eqn1BC(a+br)2+(br)2=(r+b)2a2+b2+r2+2ab2ar2br+b22br+r2=r2+2br+b2a2+2b2+2r2+2ab2ar4brr22brb2=0a2+b2+r2+2ab2ar6br=0....eqn2r22raa2=2rbb2frlm1r22ar+a2=6br2abb2from2r22ra+b2=a2+2rbr22ra+b2=6br2aba2soa2+2rb=6br2aba22a24br+2ab=0r=2a2+2ab4b=a(a+b)2br22ara2=2rbb2(a2+ab2b)22(a+b)(a2+ab2b)=a2b2a2(a+b)24b2(a+b)(a+b)ab=(a+b)(ab)devidingbya+bbothsidea2(a+b)4b2a(a+b)b=ab(a+b)(a24b2ab)=aba24b2ab=aba+bletab=kk24k=k1k+1k24k4=k1k+1k34k2+k24k=4k4k33k28k+4=0

Commented by tanmay.chaudhury50@gmail.com last updated on 19/Jan/19

Commented by tanmay.chaudhury50@gmail.com last updated on 19/Jan/19

k=(a/b)=0.438   so   a=0.438b  (a/b)=4.562   a=4.562b →this solution not feasible  from diagram...

k=ab=0.438soa=0.438bab=4.562a=4.562bthissolutionnotfeasiblefromdiagram...

Commented by tanmay.chaudhury50@gmail.com last updated on 19/Jan/19

r=((a(a+b))/(2b))=((0.438b(0.438b+b))/(2b))=0.219(1.438b)  r=0.3149b

r=a(a+b)2b=0.438b(0.438b+b)2b=0.219(1.438b)r=0.3149b

Answered by ajfour last updated on 19/Jan/19

i obtain       a= b((√2)−1)       r= (2+(√2)−2(√(1+(√2))) )b .

iobtaina=b(21)r=(2+221+2)b.

Answered by ajfour last updated on 19/Jan/19

From △AEC_(−)   (b−r)^2 +r^2 = (a+r)^2     ...(i)   BC^2  =(b+r)^2 = (a+b−r)^2 +(b−r)^2                                                    ....(ii)  ⇒ r^2 −2(a+b)r+b^2 −a^2 = 0   &        r^2 −2(a+3b)r+(a+b)^2 = 0  comparing the two        ((a+b)/(a+3b)) = ((b−a)/(a+b))  ⇒   a^2 +2ab+b^2 = 3b^2 −a^2 −2ab  or    a^2 +2ab+b^2  = 2b^2   ⇒    a+b = b(√2)           a = ((√2)−1)b .  now picking up the 2^(nd)  quadratic in r        r^2 −2(a+3b)r+(a+b)^2 = 0  but we found  a=(√2)b−b , so    r^2 −2(b(√2)−b+3b)r+2b^2 = 0     r^2 −2(2+(√2))b+2b^2  = 0  ⇒  r =( 2+(√2)±(√((2+(√2))^2 −2)) )b  feasible one for diagram is         r = (2+(√2)−2(√(1+(√2))) )b  .

FromAEC(br)2+r2=(a+r)2...(i)BC2=(b+r)2=(a+br)2+(br)2....(ii)r22(a+b)r+b2a2=0&r22(a+3b)r+(a+b)2=0comparingthetwoa+ba+3b=baa+ba2+2ab+b2=3b2a22abora2+2ab+b2=2b2a+b=b2a=(21)b.nowpickingupthe2ndquadraticinrr22(a+3b)r+(a+b)2=0butwefounda=2bb,sor22(b2b+3b)r+2b2=0r22(2+2)b+2b2=0r=(2+2±(2+2)22)bfeasibleonefordiagramisr=(2+221+2)b.

Commented by mr W last updated on 20/Jan/19

sir, i don′t think we can get        ((a+b)/(a+3b)) = ((b−a)/(a+b))  from        r^2 −2(a+b)r+b^2 −a^2 = 0   &        r^2 −2(a+3b)r+(a+b)^2 = 0.    let′s look at  a_1 x^2 +b_1 x+c_1 =0  a_2 x^2 +b_2 x+c_2 =0  if both eqn. have two equal roots,  then  (a_1 /a_2 )=(b_1 /b_2 )=(c_1 /c_2 )  if both eqn. have only one equal root,  we can not say  (a_1 /a_2 )=(b_1 /b_2 )=(c_1 /c_2 )  i think we have here the second case.

sir,idontthinkwecangeta+ba+3b=baa+bfromr22(a+b)r+b2a2=0&r22(a+3b)r+(a+b)2=0.letslookata1x2+b1x+c1=0a2x2+b2x+c2=0ifbotheqn.havetwoequalroots,thena1a2=b1b2=c1c2ifbotheqn.haveonlyoneequalroot,wecannotsaya1a2=b1b2=c1c2ithinkwehaveherethesecondcase.

Terms of Service

Privacy Policy

Contact: info@tinkutara.com